Mission: impossible III [videorecording (DVD)] - Abrams, J. J. (Jeffrey Jacob), 1966-; Cruise, Tom, 1962-; Hoffman, Philip Seymour, 1967-2014; Rhames, Ving, 1961- (Paramount Pictures, 2006)
Ethan Hunt has retired from active duty as a super-spy in order to train new IMF agents. He is called back into action to confront the toughest villain he has ever faced - Owen Davian, an international weapons and information provider with no remorse and no conscience. Hunt assembles his team - Luther Strickell, transportation expert Declan, and background operative Zhen , in order to rescue Lindsey, one of his trainees, who was kidnapped while on a surveillance detail of Davian. It soon becomes evident that Davian is well-protected, well-connected, and downright malicious, forcing Hunt to extend his journey back into the field in order to rescue his wife, Julia, and uncover an IMF double agent in the process.